Risk of contralateral nodal failure following ipsilateral IMRT for node-positive tonsillar cancer. (December 2017) - Gottumukkala, Sujana; Pham, Nhat-Long; Sumer, Baran; Myers, Larry; Truelson, John; Nedzi, Lucien; Khan, Saad; Hughes, Randy; Sher, David J.
Highlights: Ipsilateral IMRT for N+ tonsil cancer has a very low risk of contralateral failure. Ipsilateral IMRT is associated with a highly favorable toxicity profile. Ipsilateral IMRT should be therefore be considered even for bulky nodal disease. Abstract: Purpose: To determine the risk of contralateral nodal failure following ipsilateral radiotherapy in a series of patients with node-positive tonsillar squamous cell carcinoma. Methods: Retrospective review was used to identify 34 patients with well-lateralized node-positive tonsillar squamous cell carcinoma treated with definitive or adjuvant radiation to the primary site and ipsilateral neck between 2005 and 2015. Contralateral nodal failure, locoregional recurrence, distant metastasis, and overall survival were calculated using actuarial and/or cumulative incidence statistics. Results: At last follow-up, contralateral nodal failure was only observed in 1 patient (3%) with N1 disease. At median follow-up of 34 months for surviving patients, the 3-year overall survival probability was 87%, and the 3 year cumulative incidences of locoregional failure and distant metastasis were 6.5% and 7.2%, respectively. No disease-free patient was permanently gastrostomy-dependent. Conclusion: Ipsilateral radiation treatment with IMRT is effective in node-positive patients with well-lateralized tonsillar cancer, resulting in a low risk of contralateral regional recurrence, even in patients with N2b disease.